Pengaruh Metode Pembelajaran, Media Pembelajaran dan Kemampuan Guru Menggunakan IT Terhadap Hasil Belajar Siswa SD Muhammadiyah Kota Probolinggo - Suci Rahayu, Prasetyaning (LP3M UNZAH GENGGONG, 2021)
Abstract Departing with the idea of ​​wanting to improve learning services using IT (Laptops and Projectors), and the use of learning methods, and measuring the ability of SD Muhammadiyah Probolinggo teachers on student learning outcomes at SD Muhammadiyah Probolinggo, this research was conducted. Based on the problems mentioned above, it is necessary to have a strategy to improve optimal learning services with interesting methods from innovative teachers in motivating students' creativity, namely social studies learning through visual media in the form of IT media. Keywords: learning services, learning through, interesting methods, student learning